Ricardo as Spinoza Secularization, Semitism, and Political Economy - Brody, Samuel Hayim (2023)
Although the story that the great political economist David Ricardo (1772-1823) learned at the same school as Spinoza is most likely a romantic fiction, it suggests an intriguing parallel that reaches far beyond mere biographical coincidence. Like Spinoza, Ricardo was seen by both admirers and detractors as contributing in a "Jewish" way to forging a new, secular sphere of modern life. Because he left the Jewish community and did not frame his intellectual work as deriving from Judaism, such arguments necessarily appealed to racialization, making Ricardo Jewish in spite of himself. Considering Ricardo as a Spinoza figure offers us a deeper perspective on the role of racialized Jewishness in narratives of modern social science and thereby also in the theory of secularization.